Introducing Microsoft SQL Server 2016 mission-critical applications, depper insights, hyperscale cloud - Varga, Stacia; Cherry, Denny; D'Antoni, Joseph (Microsoft Press, 2016)
With Microsoft SQL Server 2016, a variety of new features and enhancements to the data platform deliver breakthrough performance, advanced security, and richer, integrated reporting and analytics capabilities. In this ebook, we introduce new security features: Always Encrypted, Row-Level Security, and dynamic data masking; discuss enhancements that enable you to better manage performance and storage: TemDB configuration, query store, and Stretch Database; review several improvements to Reporting Services; and also describe AlwaysOn Availability Groups, tabular enhancements, and R integration.